2015
DOI: 10.1097/gme.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Dietary isoflavones and bone mineral density during midlife and the menopausal transition

Abstract: Objective To examine the cross-sectional and longitudinal relations between dietary intake of isoflavones and BMD of the lumbar spine (LS) and femoral neck (FN) in Black, White, Chinese and Japanese women during the menopause transition (MT). Methods We tested whether tertiles of isoflavone intake were associated with baseline BMD, when all women were pre- or early perimenopausal. To analyze whether isoflavone intake was associated with longitudinal BMD, we fit piece-wise linear models to repeated measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In SWAN women, levels of serum 25-hydroxy vitamin D below 20 ng/mL at the third follow up visit (when mean age was 48.5 years) were associated with 85% higher hazard for incident non-traumatic fractures 59 . Greater intake of isoflavones (such as from soy products) was also associated with greater BMD at the baseline visit 60,61 . However, more of a good thing is not always better.…”
Section: Summary and Clinical Implicationsmentioning
confidence: 93%
“…In SWAN women, levels of serum 25-hydroxy vitamin D below 20 ng/mL at the third follow up visit (when mean age was 48.5 years) were associated with 85% higher hazard for incident non-traumatic fractures 59 . Greater intake of isoflavones (such as from soy products) was also associated with greater BMD at the baseline visit 60,61 . However, more of a good thing is not always better.…”
Section: Summary and Clinical Implicationsmentioning
confidence: 93%
“…Various lignans found in plant cell walls and fiber-rich foods and seeds, had a positive effect on cognition and markers of AD induced in mice [ 65 , 66 , 67 , 68 , 69 ]. It has been shown that higher dietary lignan intake may be associated with better cognitive function [ 70 , 71 ], while no improvement in cognitive performance was observed when consuming coumestrol [ 72 ]. However, dietary intake of isoflavones showed no association with cognition [ 70 ].…”
Section: Neuroprotective Effects Of Selected Phytoestrogensmentioning
confidence: 99%
“…Therefore, evidence of a beneficial effect of isoflavones and other phytoestrogens on bone mineral density in post-menopausal and peri-menopausal women are still limited (Greendale et al, 2015).…”
Section: Osteoporosismentioning
confidence: 99%